2012
DOI: 10.1186/1297-9716-43-51
|View full text |Cite
|
Sign up to set email alerts
|

Duration of protective immunity and antibody responses in cattle immunised against alcelaphine herpesvirus-1-induced malignant catarrhal fever

Abstract: Protection of cattle from alcelaphine herpesvirus-1 (AlHV-1)-induced malignant catarrhal fever (MCF) has been described previously, using an attenuated virus vaccine in an unlicensed adjuvant. The vaccine was hypothesised to induce a protective barrier of virus-neutralising antibody in the oro-nasal region, supported by the observation of high titre neutralising antibodies in nasal secretions of protected animals. Here we describe further analysis of this vaccine strategy, studying the effectiveness of the vac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
44
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 33 publications
(46 citation statements)
references
References 34 publications
2
44
0
Order By: Relevance
“…25,118 Currently, there is renewed interest in vaccination for this group of viruses, a goal long thought out of reach due to discouraging results in the 1970s and 1980s. 32,75,118,125,126 It is now clear that some dead-end host species recover, 92,93,153 corroborating clinical suspicions from the late 1920s and early 1930s that MCF is not invariably fatal. Important differences exist between the ecology of sheep-and wildebeest-associated MCF.…”
mentioning
confidence: 81%
“…25,118 Currently, there is renewed interest in vaccination for this group of viruses, a goal long thought out of reach due to discouraging results in the 1970s and 1980s. 32,75,118,125,126 It is now clear that some dead-end host species recover, 92,93,153 corroborating clinical suspicions from the late 1920s and early 1930s that MCF is not invariably fatal. Important differences exist between the ecology of sheep-and wildebeest-associated MCF.…”
mentioning
confidence: 81%
“…The antibody titre in protected animals did not rise significantly after challenge suggesting that virus was unable to penetrate the mucosal barrier and boost the response. Conversely, in vaccinated animals that succumbed to MCF, the antibody titre rose significantly after challenge, indicating successful virus entry and stimulation of an anamnestic response that was not protective (Russell et al, 2012;Parameswaran et al, 2014). This study also showed that in a few animals, protection from MCF was found despite the generation of little or no neutralising antibody, suggesting that immune mechanisms other than virus-neutralising antibody may influence protection from AlHV-1 (Parameswaran et al, 2014).…”
Section: Introductionmentioning
confidence: 68%
“…AlHV-1 that has been propagated in culture for up to five passages is capable of inducing MCF in susceptible species such as cattle and certain laboratory animals but further laboratory passage of the virus leads to the attenuation of pathogenicity and is accompanied by rearrangements of the virus genome (Wright et al, 2003). Attenuated strains of AlHV-1 have been used as the basis for all serological tests for MCF described to date Li et al, 1994;Russell et al, 2012) and the attenuated strain of AlHV-1 C500 at passage >1000 has been used as a candidate vaccine that could protect cattle from intranasal challenge with a fatal dose of pathogenic AlHV-1 in experimental trials Russell et al, 2012). In susceptible species, primary, transient viral replication appears to occur within lung epithelium, after which the virus disseminates systemically .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Many deer die within 48 hr of the first clinical signs and affected bison generally die within 3 days (O'Toole et al, 2002). In contrast, mortality seen in cattle can occur within a few days or weeks after the first clinical signs (Russell et al, 2012).…”
Section: Malignant Catarrhal Fevermentioning
confidence: 99%